Fostering the usage of flipped classroom: student engagement, student content interaction and student motivation / Yusrina Hayati Nik Muhammad Naziman … [et al.] - Nik Muhammad Naziman, Yusrina Hayati; Mohd Aznan, Nadia Farleena; Ab Rahman, Siti Maziah; Md Nor, Nor Haryanti; Idrus, Syukurriah (2019)
Teaching and learning nowadays is different from past. Together with their environment where the students can easily connected to internet and digital media make them ease to be technology savvy. Thus, flipped classroom become the option to the lecturer to change methods of teaching. However, there are lacked discussions in innovating teaching approach particularly in marketing. Hence, the objectives of this study to examine factors influencing the usage of flipped classroom and which factors contribute most to the usage of flipped classroom. The sampling of the data used is sample random sampling. The researcher will used the structured questionnaire and divided into five sections including the demographic section. The study will analyze normality test, data cleaning, reliability test, descriptive and frequency analysis, Pearson correlation and Multiple Regression to test the hypothesis. Apparently, the expected result will be used to recommend in order having better understanding in student’s learning particularly in using technology.